Greywater treatment in a green wall using different filter materials and hydraulic loading rates. (15th August 2023) - Sami, M.; Hedström, A.; Kvarnström, E.; McCarthy, D.T.; Herrmann, I.
Abstract: Green walls in urban environments can be both an aesthetic feature and be of practical use in greywater treatment. This study evaluates the effect of different loading rates (4.5 l/d, 9 l/d, and 18 l/d) on the efficiency of treating actual greywater from a city district in a pilot-scale green wall with five different filter materials as substrates (biochar, pumice, hemp fiber, spent coffee grounds (SCG), and composted fiber soil (CFS)). Three cool climate plant species, Carex nigra, Juncus compressus, and Myosotis scorpioides, were chosen for the green wall. The following parameters were evaluated: biological oxygen demand (BOD), fractions of organic carbon, nutrients, indicator bacteria, surfactants, and salt. Three of the five materials investigated – biochar, pumice, and CFS - showed promising treatment efficiencies. The respective overall reduction efficiencies of BOD, total nitrogen (TN) and total phosphorus (TP) were 99%, 75%, and 57% for biochar; 96%, 58%, and 61% for pumice; and 99%, 82% and 85% for CFS. BOD was stable in the biochar filter material with effluent concentrations of 2 mg/l across all investigated loading rates. However, higher loading rates had a significantly negative effect on hemp and pumice for BOD. Interestingly, the highest loading rate (18 l/d) flowing over pumice removed the highest levels of TN (80%) and TP (86%). Biochar was the most effective material in removing indicator bacteria, with a 2.2–4.0 Log10 reduction for E. coli and enterococci. SCG was the least efficient material, giving a higher BOD in the effluent than in the influent. Therefore, this study presents the potential of natural and waste-derived filter materials to treat greywater effectively and the results can contribute to the future development of nature-based greywater treatment and management practices in urban areas. Highlights: Higher HLRs affected the BOD reduction by hemp and pumice, unlike biochar. All filter materials except spent coffee grounds reduced >82% of BOD at different HLRs. High nitrogen (80%) and phosphorus (86%) removal by pumice at the highest HLR. Composted fiber soil had higher treatment performance than spent coffee grounds. Effective E. coli and enterococci removal achieved by biochar at the lower HLRs.